1991
DOI: 10.1590/s0036-46651991000400008
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of acute respiratory diseases in Rio de Janeiro: occurrence of respiratory viruses during four consecutive years

Abstract: The occurrence of different viruses in nasopharyngeal secretions from children less than 5 years old with acute respiratory infections (ARI) was investigated over a period of 4 years (1982-1985) in Rio de Janeiro. Of the viruses known to be associated with ARI, all but influenza C and parainfluenza types 1, 2 and 4 were found. Viruses were found more frequently in children attending emergency or pediatric wards than in outpatients. This was clearly related to the high incidence of respiratory syncytial virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
1
35

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 6 publications
9
43
1
35
Order By: Relevance
“…This finding differs from data reported by other Brazilian and South American studies, which indicate Ad as the second most prevalent virus in ARI observed in hospitalized children (Nascimento et al 1991, Kajon et al 1999, Larrañaga et al 2000, Straliotto et al 2002. In this study the rate of ARI by Ad in hospitalized patients was 1.6%, while in other studies this rate ranged from 3.3% to 12.6% (Larrañaga et al 2000, Hong et al 2001, Tsai et al 2001, Chen et al 2004.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding differs from data reported by other Brazilian and South American studies, which indicate Ad as the second most prevalent virus in ARI observed in hospitalized children (Nascimento et al 1991, Kajon et al 1999, Larrañaga et al 2000, Straliotto et al 2002. In this study the rate of ARI by Ad in hospitalized patients was 1.6%, while in other studies this rate ranged from 3.3% to 12.6% (Larrañaga et al 2000, Hong et al 2001, Tsai et al 2001, Chen et al 2004.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover those infections showed a high case fatality rate of 25%. During the twelve months of study, Ad infections were observed year round without a clear seasonality as it was observed in other Brazilian cities and in other tropical countries (Arruda et al 1991, Nascimento et al 1991, Shek & Lee 2003, Tsuchiya et al 2005.…”
Section: Discussionmentioning
confidence: 60%
“…Brazilian studies of viral ARI mention a possible interregional variation. Annual outbreaks of HPIV-3 infections in children living in a shanty town in Rio de Janeiro city were observed during the late winter or spring [34]. In a three-year-study conducted in Porto Alegre, a city located in the South of Brazil, only 10 cases of HPIV-3 were identified out of a total of 862 infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Brazil reinforce the importance of HAdVs in ARD cases and they have been found as the second most frequent virus detected in nasopharyngeal aspirates (NPA) from children with ARDs in the cities of São Paulo (Moura et al 2007) and Rio de Janeiro (Nascimento et al 1991), located in South-eastern Brazil and Porto Alegre (Straliotto et al 2002), located in Southern Brazil.…”
mentioning
confidence: 91%